EXPERIENCE OF «SCHOOL OF HEALTH» AND A ROLE OF THE GENERAL PRACTITIONER IN THE STRUGGLE WITH RISK FACTORS OF ISCHEMIC HEART DISEASE - N. M. Nurillaeva; A. G. Gadaev (Рациональная фармакотерапия в кардиологии)
Aim. To study dynamics of risk factors of ischemic heart disease (IHD) in patients trained in "School of Health" by general practitioners (GP) of rural medical office (RMO) and family outpatient clinic (FOC).  Material and methods. Patients (n=67, aged 56.1±0.9) with stable angina and IHD risk factors were examined. All patients were trained in 3 "Schools of Health" in the city of Tashkent and rural Surkhandarya region. Follow-up duration was 2 years (2008-2010). Results. During 2 years of follow-up significant reduction in influence of IHD risk factors was found in patient according to elaborated mathematic model: dyslipidemias in 40.3%, improper feeding in 25.3%, anxiety-depressive disorders in 14.6%, low physical activity in 7.4%, smoking in 6.6%. Conclusion. Organization of the "School of Health" by GP in RMO and FOC is rational and usage of training programs for struggle with IHD risk factors is effective.